Development of quality digital innovation by optimally utilizing company resources to increase competitive advantage and business performance - Saiful Hidayat; Margono Setiawan; Fatchur Rohman; Ananda Sabil Hussein (Administrative Sciences, 2022)
Purpose: This study aims to find out how to increase the competitive advantage of a company through the development of digital innovation that utilizes company resources optimally to improve business performance. Namely, the aim is to examine the effect of company resources on digital innovation and business performance, and the effect of company resources on business performance through digital innovation. Methods: This study uses a quantitative research approach. Observations were made in a cross-section/one shot in 2022. The population of this study was the ISP industry in Indonesia, which amounted to 474 companies, and the unit of observation was the management. Samples were taken from 240 respondents. This study used structural equation modeling (SEM) to test the causality correlational relationship between constructs. Results: The hypothesis testing shows that company resources have a significant direct effect on business performance, and company resources have a significant indirect effect on business performance through digital innovation. The indirect effect of company resources on business performance through digital innovation is more dominant than the direct effect of company resources on business performance. Conclusions: Improving business performance and competitive advantage will be better achieved by optimizing the utilization of the company's existing resources to develop digital innovation, compared to directly increasing the company's resources to improve business performance.
Keywords: 350; business performance; company resources; competitive advantage; digital innovation; internet service provider